Influence of Heat Input on Microstructure and Mechanical Properties of Laser Weld Metal in 2507 Duplex Stainless Steel by Different Welding Speed and Welding Power - Shuai ZHAO; Yaxuan BI (Medžiagotyra, 2024)
This manuscript attempts to explore the macroscopic morphology microstructural aspects and mechanical properties of different laser welding speed and power on the 2.5 mm thick DSS welding joint. Through the evaluation of 12 groups samples with different welding parameters, we found that the optimal laser welding process parameters were a welding speed of 6mm/s, laser power of 1.6 kW and welding speed of 8 mm/s, laser power of 1.7 kW. When the heat input was 2.125 kJ/cm, the content of ferrite and austenite was relatively uniform, and the ratio was close to 1:1. We found that the hardness of the weld metal zone was slightly higher than that of the base metal, with an average value of 330 HV. When the heat input was 2.125 kJ/cm, the microhardness of welded joint was better than other parameters, reaching 400 HV in the welding metal zone. The tensile strength of the weld was enhanced with the increase of heat input, and the maximum was 900 MPa. Through SEM analysis, the fracture locations of tensile specimens were all in the weld zone, and the fracture morphology had a large number of dimples, belonging to the ductile fracture.